"Exploration of the influence that planning has into the learning of the second language with the students of Noveno Año de Educación General Básica "A" at Unidad Educativa “Alfredo Pérez Guerrero”, city of Guano, Chimborazo province, during the school term October 2016- March 2017" - Cauja Shagñay, Vanessa Elizabeth (2017)
A previous study determined that ninth year students of basic education, room “A” from an educational institution called” Alfredo Pérez Guerrero” showed little motivation to learn English. It was executed with students of ninth of basic education, room “A” from an educational institution called” Alfredo Pérez Guerrero” in the first term ( quimestre) during the school year 2016-2017. The purpose of this study was to describe how the planning of a class influences the learning of English. The type of study is qualitative with an exploratory level. The research was carried out with a population of twenty students where ten are men, ten are women and a teacher. The qualitative method employed was the ethnographic. The technique applied was the non-structured observation along with a survey as researches played a passive role; the instrument for data collection was a questionnaire with 10 questions elaborated by the investigator. After the analysis of the data, it can be said that a poor planning of a class influences the learning of English as students do not feel motivated to learn, the class becomes boring and shows little teacher´s preparation when he or she conducts a class.